Report of Inter Ministerial Group Simplification of Customs Procedures in Air Cargo and Airports - Planning Commission (Planning Commission, 2005)
This Report is aimed at streamlining customs procedures at India's major airports with a view to reducing the dwell time of cargo and associated costs. Air cargo is becoming an increasingly important dimension of India's growing trade. In fiscal year 2005-06, Indian exports crossed $101 billion, representing an annual growth of 25% over 2004-05. Similarly, imports crossed $140 billion in the same year. Though some improvements have been witnessed in the recent past, numerous bottlenecks to trade persist. As a result, the dwell time of cargo at Indian airports is significantly longer than that in other major airports in Asia. This compromises the competitiveness of Indian industry, reducing trade potential and, therefore, needs to be addressed as a priority.
Planning Commission Government of India
Planning Commission Government of India